Large-Area Photoreceptor Degeneration Model in Rabbits by Photocoagulation and Oxidative Stress in the Retina - Wang, Zhexuan; Feng, Chenli; Yang, Ruyi; Liu, Tingting; Chen, Yin; Chen, Aihua; Yan, Biao; Yuan, Yuanzhi; Zhang, Jiayi (Frontiers in Neuroscience, 2021)
Photocoagulation is used for the treatment of retinal ischemic disease. However, due to the invasive nature of photocoagulation and variety of melanin concentrations between individuals, it would be challenging in avoiding damages of the adjacent photoreceptors and inducing several side effects. Previous studies indicated the role of laser power, duration and spot size on retinal lesion, but the effect of inter-spot distance of the laser pulses need to be considered in panretinal photocoagulation. In this study, we examined different parameters of photocoagulation on the lesion of retina in rabbit, finding that the lesion level of out nuclear layer of the retina depended on the pulse duration and laser spot size, and decreasing inter-spot distance could completely abolish the photoreceptor layer. The degeneration of photoreceptor by photocoagulation occurred in 24 hours and did not restore afterwards. We then conducted panretinal photocoagulation in rabbit and found that oxidative stress was decreased in inner nuclear layer of retina, and pupillary light reflex and ERG signals were impaired. Our study could provide a rabbit model to explore mechanism in photoreceptor degeneration and therapies for the side effects after photocoagulation.